PKM: Penyuluhan tentang Peningkatan Pengelolaan Sumber Daya Manusia pada Muda Tama Gallery, Tumang, Boyolali - Fadilah, Novi Siti; Pujiani, Dewi; Sarsiti, Sarsiti; Trisnowati, Juni; Suryati, Suryati; Praptiestrini, Praptiestrini; Rohwiyati, Rohwiyati; Widiastuti, Erni; Danarwati, Yanti Sri; Surendra, Arya (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The aim of this community service is to identify the problems of the partner, Copper Crafts Muda Tama Gallery, Tumang, Boyolali and provide scientific solutions. The service team identified that the number of craftsmen was starting to decline due to the tendency of the younger generation to prefer to pursue business as marketers. The team uses the extension method to share knowledge with partner communities. Human Resources Management can be carried out in several ways apart from continuing to maintain good direction efforts at each stage of production, establishing controlled production procedures, evaluating employee work results, and developing employees in terms of reward and punishment; The service team proposed that the company collaborate with several vocational schools with a concentration in arts and crafts. This is important so that this skill does not become extinct, and in fact so that it can grow in terms of manufacturing and the number of craftsmen. The result of this activity is an increase in the understanding of partners (owners of Muda Tama Gallery) in managing human resources so that there is no shortage/loss of craftsmen. Another output is an article in this journal